Flood susceptibility mapping based on watershed geomorphometric characteristics and land use/land cover on a small island - B.H. Narendra; O. Setiawan; R.A. Hasan; C.A. Siregar; , Pratiwi; N. Sari; A. Sukmana; I.W.S. Dharmawan; R. Nandini (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Flooding is the most frequent hydrological disaster which greatly impacts humans and the environment. Lombok, a small tropical island, experiences severe flooding almost yearly. Flood susceptibility mapping is important to determine the priority watershed in implementing flood mitigation action, including improving the spatial planning in watershed management. Several methods of determining flood susceptibility require the support of long data series and a variety of monitoring equipment in the field where not every region has the resource capacity. Compared to other methods that require the support of long data series and a large number of evenly distributed monitoring equipment, the geomorphometric parameters and land use/cover in a watershed are closely related to the hydrological responses and are potentially applicable in flood susceptibility mapping. This research aimed to classify the watershed flood susceptibility on a small island based on the geomorphometric characteristics and land use/land cover of the watershed.METHODS: This study was carried out on Lombok Island, located in southern Indonesia, representing a small island in the tropical region. Watershed classification was carried out using 24 geomorphometric variables and land use/land cover, representing aspects of the river network, geometry, texture, and watershed relief. The principal component analysis approach was carried out to determine the most significant variable, and the weight of each variable was determined using the weighted sum approach method. Then, compound values were calculated based on the weighted values and preliminary ranking to indicate the flood susceptibility levels, which were divided into five classes.FINDINGS: The analysis found that the variables most related to flood events are the total number of rivers, relief ratio, elongation ratio, river density, stream frequency, and dry agricultural land use. These most related geomorphometrics indicate that the watersheds with higher flood susceptibility have low rock permeability, relatively low infiltration capacity, and relatively high surface runoff, thus triggering flooding. The flood susceptibility mapping classified 16 watersheds as having very high flood susceptibility. This research shows that analysis of the geomorphometric characteristics and land use/land cover can be relied upon to determine the flood susceptibility level, which is useful in spatial planning and flood disaster mitigation.CONCLUSION: Geomorphometric characteristics and land use/land cover can be used to determine a watershed's hydrological characteristics or behaviour. Based on the geomorphometric characteristics of the watersheds on Lombok Island, some identifying variables that are highly related to flood processes were obtained. Based on these characteristics, watersheds with high and very high flood susceptibility levels have low rock permeability, relatively low potential infiltration capacity, and relatively high surface runoff potential. Flooding still occurs despite good forest cover because the geomorphometric characteristics of the watershed also play a major role in flood events.